Deploy a Microservice Application using Docker Compose - Pallavi Priya Patharlagadda (North American Journal of Engineering Research, 2020)
The deployment of microservices as Docker containers is examined in this paper. Kubernetes pods are used to deploy the containers after they have been orchestrated using Docker compose and Docker swarm. We go over how these technologies make microservices architectures scalable and easy to deploy. We illustrate the advantages of using these tools in contemporary software development with real-world examples and insights. By leveraging Docker for containerization and Docker Compose for the management of multi-container applications, our investigation demonstrates how these tools can be used to create microservice architectures that are resilient, scalable, and Flexible